Selected Papers from the XXIII World Congress of Philosophy (Philosophy Documentation Center, 2015)
The twenty-third World Congress of Philosophy was held in Athens in 2013. It was sponsored by the Greek Philosophical Society, in cooperation with the Fédération Internationale des Sociétés de Philosophie. This volume contains outstanding papers presented at the plenary session, symposia, and Endowed Lecture sessions of this congress. It has been published in both print and electronic formats as a special supplement to the Journal of Philosophical Research. Print copies are also available from Amazon. Contributors include Simon Critchley, Souleymane Bachir Diagne, Umberto Eco, Dagfinn Føllesdal, Jürgen Habermas, Wenchao Li, Alexander Nehamas, and Ernest Sosa.